2019
DOI: 10.1590/s1677-5538.ibju.2018.0186
|View full text |Cite
|
Sign up to set email alerts
|

A higher circulating concentration of 25-hydroxyvitamin-D decreases the risk of renal cell carcinoma: a case-control study

Abstract: Objective:To investigate the relationship between vitamin D status, using circulating 25-hydroxyvitamin D [25 (OH) D], and renal cell carcinoma (RCC) risk in a case-control study, because the association between the two is unclear in China.Materials and Methods:A total of 135 incident RCC cases were matched with 135 controls by age and sex. The blood samples were collected on the first day of hospitalization before surgery to measure plasma 25 (OH) D. Logistic regression analyses were used to calculate odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Since, it has been shown that the reduction in the vitamin D level is strongly linked to increased mortality rates from cancer. In addition, cancer incidence rates substantially reduced by sufficient amount of the main circulatory form of vitamin D, 25(OH) D [ [15] , [16] , [17] , [18] , [19] , [20] , [21] ].…”
Section: Discussionmentioning
confidence: 99%
“…Since, it has been shown that the reduction in the vitamin D level is strongly linked to increased mortality rates from cancer. In addition, cancer incidence rates substantially reduced by sufficient amount of the main circulatory form of vitamin D, 25(OH) D [ [15] , [16] , [17] , [18] , [19] , [20] , [21] ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, breast cancer accounts for 30% of the all newly diagnosed cancer cases in women [3].Vitamin D is a steroid derivative, and plays a key role in promoting bone growth. Epidemiological studies have shown that low serum vitamin D levels was linked to a higher risk of colon and bladder cancer, and higher circulating concentration of 25(OH)D decreased the risk of renal cell carcinoma [4][5][6]. Additionally, an anticancer effect on vitamin D against breast, prostate, and colorectal cancers have been reported [7].…”
mentioning
confidence: 99%
“…Interestingly, this study did not report an increased risk of pancreatic cancer among people with 25(OH)D > 100 nmol/L. Li et al conducted a case-control study in the Chinese Han population in which they found the protective effect of higher 25(OH)D levels against renal cell carcinoma [ 214 ]. To sum up, the available results of clinical trials, mainly observational, do not allow one to unambiguously state that supplementation with vitamin D reduces the risk of cancer.…”
Section: What Do We Know So Far About Vitamin D In Cancer Prevention and Prognosis From Clinical Trials?mentioning
confidence: 94%